Relationship between feed efficiency, milk yield, rumination rate and faecal glucocorticoids in dairy cows - Tennant, L.J. (2018)
With improved knowledge of rumen function and the animal’s response to changes, we can better understand true feed efficiency within a dairy herd. Feed efficiency within a dairy herd is likely to be increased by minimising stress. One potential stressor is a change in diet composition, which may also affect rumen function and performance. In this work, effects of diet change on non-invasive indicators of rumen function and stress were investigated. Rumen function was assessed through feed intake, milk yield, feed conversion efficiency, rumination rate, digestibility and methane emissions. Stress was assessed through faecal glucocorticoid concentration. Faecal glucocorticoids are metabolites of cortisol, providing a non-invasive alternative to blood cortisol for evaluating stress. An ELISA method was used to quantify the faecal glucocorticoid metabolite 11-Oxoetiocholanolon. This assay is specific for cortisol metabolites. To change faecal glucocorticoids, 26 cows were subjected to a mild stress event. Faecal samples were collected by rectal grab sampling before this event as a basal measurement and at 10-12 hours post stress event (to allow time for gut passage). In the first trial of time of day had no effect on faecal glucocorticoid concentration, but faecal glucocorticoid concentration increased (P<0.001) 10-12 hours after mild stress events (blood sampling, ear tagging, and hoof trimming), thereby confirming faecal glucocorticoid concentration as an indicator of stress. In Experiment 1, 37 cows were used to examine responses to changes in diet. Four diets containing distillers dried grains with soluble (DDGS) at 0, 80, 120, and 160 g/kg diet DM were fed to cows in a 4x4 Latin square experimental design. Faecal samples were collected 24 hr after each of the four dietary changes for glucocorticoid determination. Rumination, milk yield, feed conversion efficiency, dry matter intake, faecal acid insoluble ash and methane were recorded for each individual cow. Diet DDGS inclusion level did not affect faecal glucocorticoid concentration, but mean faecal glucocorticoid concentration increased (P<0.001) with each successive diet change across Periods 1 to 4, suggesting a cumulative mild stress response. Diet composition and diet change did not affect indicators of rumen function. In Experiment 2, 39 cows were used to examine responses to changes in diet. Four diets containing different sources of rumen-protected protein were fed to cows in a 4x4 Latin square experimental design. Faecal samples were collected 12 hr and 24 hr after each of the four dietary changes. Rumination, milk yield, feed conversion efficiency, dry matter intake, faecal acid insoluble ash and methane were recorded for each individual cow. Diet composition and diet change did not affect rumen function. Diet composition did not affect faecal glucocorticoid concentration, and mean faecal glucocorticoid concentration did not increase significantly with successive diet changes across periods. In Experiment 1 faecal glucocorticoid concentration was negatively correlated with feed conversion efficiency (Y=-227.3*X+902.3, P=0.03, r=0.028); in Experiment 2, however, no correlation was found. Results of this work indicate that mild stress events, such as blood sampling, ear tagging and hoof trimming, cause an increase in faecal glucocorticoid concentration, suggesting a stress response. In Experiment 1, faecal glucocorticoid concentration increased with successive periods, but not with dietary changes, which did not affect rumen function. In Experiment 2, there was no change in faecal glucocorticoid concentration with period or dietary changes, which did not affect rumen function. It is concluded that the faecal glucocorticoid method is sensitive enough to detect responses to mild stress events, but minor changes in diet do not affect rumen function or cause stress responses.